2005
DOI: 10.1007/s10067-005-1119-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare consumption and direct costs of rheumatoid arthritis in Belgium

Abstract: The aim of this study was to compare the socioeconomic consequences of early and late rheumatoid arthritis in Belgium and to assess the patient out-of-pocket contributions. This multicentre longitudinal study in Belgium evaluated patients with rheumatoid arthritis. Early disease was defined as diagnosis since less than 1 year. At baseline sociodemographic and disease characteristics were assessed and during the following year patients recorded all healthcare- and non-healthcare-related direct costs and out-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In Belgium, direct costs reported for late RA (disease duration 12.5 yrs) were even higher – 9,946 Euro/patient/year [9]. In Germany, direct costs were similar to the Hungarian data (2,312 Euro), but indirect costs were much higher (for sick-leave 2,835 Euro/patient/year, for a disability pension 8,358 Euro/patient/year) [10].…”
Section: Resultsmentioning
confidence: 93%
“…In Belgium, direct costs reported for late RA (disease duration 12.5 yrs) were even higher – 9,946 Euro/patient/year [9]. In Germany, direct costs were similar to the Hungarian data (2,312 Euro), but indirect costs were much higher (for sick-leave 2,835 Euro/patient/year, for a disability pension 8,358 Euro/patient/year) [10].…”
Section: Resultsmentioning
confidence: 93%
“…We must also take into account an important morbidity and socio-economic impact [1,2] of this disease as well as an increased cardio-vascular mortality [3-6]. Great strides have been made on RA in recent years, including a better understanding of the genetic aspects, environmental factors and the disease's pathogenesis, at least in the Western world.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the HAQ score was compared to disease duration and amounted to 0.9 with duration of up to 2 years and 1.6 with duration of more than 10 years [7,17,19]. In the Belgian study (133 participants) patients with early RA (average duration of 0.5 year) had a HAQ score of 1.0 and patients with late RA (average 12.5 years) had a HAQ score of 1.7 [20]. Our data showed that the HAQ score was lower (average = 0.8, median = 0.6) and the results of HAQ analyzed against disease duration were better: 0.5 with duration of up to 2 years and 1.0 with duration of more than 10 years.…”
Section: Discussionmentioning
confidence: 99%